Comprehending Crisis Intervention among Helpers - Shafrin Ahmad, Nor; Nur Nadhirah Mohd Ashri, Siti (International Journal of Engineering and Technology, 2018)
Crisis applies when an individual experiences a trauma or tense situation that causes imbalance, disorganization and disorientation. Failure to oversee the crisis brings a negative impression to the whole self. This study involved 25 crisis helpers as respondents and all of them are registered counselors in Malaysia.  Data are collected through semi structured interviews.  The open questions in semi structured interview were used to identify information on 1. the meaning of crisis, 2. the process used to handle crisis intervention; 3. the model of crisis intervention used among helpers.  Results showed that respondents’ comprehending of crisis were quite accurate and varied depending on situations experienced. They also had some brief ideas on how the process should be implemented to handle crisis cases. However, only nine out of 25 helpers specifically mentioned that they used models such as Roberts’s seven stages, Gilliland six steps, Kubler Ross, Critical Incident Stress Debriefing to handle crisis intervention cases. Meanwhile, 19 helpers used counseling theories such as Cognitive Behavioral Therapy (CBT), Reality Therapy (RT), Psychological First Aid (PFA) and basic attending counseling skills. This study indicates that helpers need more knowledge and training on crisis intervention.  They also need to comprehend process to handle crisis intervention cases in appropriate and structured ways. Development of a crisis intervention model that suits Malaysia’s culture would be most preferable and later utilized as a guide for helpers and counselors in dealing with event of crisis.
Keywords: Crisis intervention; Robert’s seven stage crisis intervention model; ABC crisis intervention model